A CASE STUDY OF A 54-YEAR-OLD MAN WITH NYHA CLASS III, STAGE 2 HYPERTENSION, AND TYPE II DIABETES MELLITUS - Nopiane Rospita Ingan Ergani; Friska Anggraini Helena (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Heart failure is when the heart cannot pump enough blood to fulfill the body's needs. This disease is dangerous and can lead to death. The most common risk factors are hypertension, diabetes mellitus, and metabolic syndrome.Case Presentation: A 54-year-old man complained of shortness of breath for the last one month, which worsened during light activities and decreased when he was in a semi-sitting position. The patient had a history of hypertension and type-II diabetes mellitus for the last five years. On physical examination, the patient's blood pressure was 140/100 mmHg, respiratory rate was 25 bpm. There were paroxysmal nocturnal dyspnea, orthopnea, rales on both basal lung fields, dyspnea on exertion, ankle edema, a pansystolic murmur heard in the apex, ascites and ankle edema. Blood laboratory examination showed HbA1c 6%, chest X-ray and ECG showed cardiomegaly.Conclusion: The patient was diagnosed with NYHA Class III Heart Failure with stage 2 hypertension and type-2 diabetes mellitus and was treated with fluids, diuretics, ACE inhibitors, beta-blockers, low salt diet, restriction of fluid intake, and oral antidiabetics.